Liquid–liquid phase transfer of magnetite nanoparticles - Machunsky, Stefanie; Grimm, Philipp; Schmid, Hans-Joachim; Peuker, Urs A. (Colloids and Surfaces A: Physicochemical and Engineering Aspects)
The study presents first experimental results of the transfer of magnetite nanoparticles from an aqueous to a second non-miscible non-aqueous liquid phase. The transfer is based on the adsorption of macromolecular surfactants onto the particle surface at the liquid–liquid interface. For a successful direct phase transfer, it is essential to have cations, like ammonium ions, present in the aqueous phase as well as a threshold concentration of surfactant in the organic liquid phase. While penetrating the liquid–liquid interface, the particles are covered with the surfactant and therefore a partial de-agglomeration is initiated. Based on literature and experimental data a mechanism of surfactant adsorption is proposed. The competing adsorption of the surfactant molecules at the liquid–liquid interface leads to the formation of emulsions and therefore to a hindrance for particles passing the interface. Nevertheless a high efficiency of 100% yield can be reached using optimized process parameters for the phase transfer process.